1992
DOI: 10.1093/oxfordjournals.humrep.a137677
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study of in-vitro fertilization, gamete intra-Fallopian transfer and intrauterine insemination combined with superovulation

Abstract: The relative effectiveness of in-vitro fertilization (IVF), gamete intra-Fallopian transfer (GIFT) and intrauterine insemination (IUI) combined with superovulation in the treatment of infertility were compared in 151 couples undergoing a single cycle of treatment. Treatment was selected as appropriate (IVF for tubal disease, GIFT or IUI/superovulation for nontubal infertility) but possible bias due to non-randomization was overcome by all couples having had favourable fertilization in a previous cycle of IVF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…Sir, The recent study of Kenny (Vol 102, April 1995) drew attention to higher pregnancy rates of patients treated with GIFT than IVF, which is consistent with our local experience using a GnRHa protocol for both treatments (Mills et al 1992). However, caution should be exercised before considering GIFT as superior to IVF without some consideration of case mix and multiple pregnancy rates.…”
Section: -1992supporting
confidence: 56%
“…Sir, The recent study of Kenny (Vol 102, April 1995) drew attention to higher pregnancy rates of patients treated with GIFT than IVF, which is consistent with our local experience using a GnRHa protocol for both treatments (Mills et al 1992). However, caution should be exercised before considering GIFT as superior to IVF without some consideration of case mix and multiple pregnancy rates.…”
Section: -1992supporting
confidence: 56%
“…To date, few studies in the literature have attempted to evaluate the efficacy of assisted reproductive technology in women with endometriosis on implantation, and all report lower implantation rates (3,12,17,18). Commonly, investigators attribute the decrease in implantation and pregnancy rates due to impaired gamete quality (3)(4)(5)19).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, investigators attribute the decrease in implantation and pregnancy rates due to impaired gamete quality (3)(4)(5)19). Most recently, Arici et aL demonstrated lower implantation rates in women undergoing first cycles of IVF for endometriosis compared to patients with tubal-factor or unexplained infertility (3.1, 9.0, and 6.7%, respectively) (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisted reproductive techniques have been introduced successfully to improve its subfertile status by endometriosis (2,3). Although previous studies reported that a lower number of preovulatory follicles were induced and a subsequently lower number of oocytes obtained in women with stages III or IV endometriosis undergoing in vitro fertilization (IVF-ET) programs (4,5), some recent studies failed to find the differences (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%